Legal regulation of the employment relation (Deventer, 2000)
"Comprises 31 papers which examine labour law as the regulation of a particular kind of contractual relationship, that is, contract of employment, and of the institutional framework, including trade unions, collective bargaining, managerial hierarchies, government departments and agencies, within which it operates. Expolres a range of issues affecting employment regulation and protection in international, EU and English law, including labour law and economic theory, EU discrimination law, collective bargaining and consultation, regulation of public service, stakeholding, labour market deregulation, the impact of competition law, trade union rights, transfer of undertakings, contract law, unfair dismissal and self-regulation."